Results of distal hypospadias repair after pediatric urology fellowship training: A comparison of junior surgeons with their mentor. Issue 3 (June 2016) - Bush, N.C.; Barber, T.D.; Dajusta, D.; Prieto, J.C.; Ziada, A.; Snodgrass, W.
Summary: Background: Teaching and learning hypospadias repair is a major component of pediatric urology fellowship training. Educators must transfer skills to fellows, without increasing patient complications. Nevertheless, few studies report results of surgeons during their first years of independent practice. Purpose: To review outcomes of distal hypospadias repairs performed during the same 2-year period by consecutive, recently matriculated, surgeons in independent practice, and to compare them to results by their mentor (with >20 years of experience). Materials: Exposure to hypospadias surgery during fellowship was determined from case logs of five consecutive fellows completing training from 2007-2011. TIP was the only technique used to repair distal hypospadias. No fellow operated independently or performed complete repairs under supervision. Instead, the first 3 months were spent assisting their mentor, observing surgical methodology and decision-making. Then, each performed selected portions under direct supervision, including: degloving, penile straightening, developing glans wings, incising and tubularizing the urethral plate, creating a barrier layer, sewing the glansplasty, and skin closure. Overall fellow participation in each case was <50%. In 2011-2012, urethroplasty complications (fistula, glans dehiscence, meatal stenosis, urethral stricture, diverticulum) were recorded for consecutive patients undergoing primary distal repair by these recent graduates in their independent practices. The fellow graduating in 2011 provided 1 year of data. All patients undergoing repair during the study period were included in the analysis, except those lost to follow-up after catheter removal. Composite urethroplasty complications were compared between junior surgeons, and between junior surgeons and their mentor, with Fisher's exact contingency test. Results: Training logs indicated fellow participation ranged from 76–134 hypospadias repairs, including distal, proximal and reoperative surgeries. Post-graduation case volumes ranged from 25–68 by junior surgeons versus 136 by the mentor. With similar mean follow-up, urethroplasty complication rates were statistically the same between the former fellows, and between them versus the mentor,  ranging from 5–13%. Nearly all were fistulas or glans dehiscence. Junior surgeons reported they performed TIP as learned during fellowship, with one exception who used 7-0 polydioxanone rather than polyglactin for urethroplasty. Discussion: This is the first study directly comparing hypospadias surgical outcomes by recently graduated fellows in independent practice with those of their mentor. We found junior surgeons achieved similar results for distal TIP hypospadias repair. Although their participation during training largely comprised observation and surgical assistance, with discrete performance of key steps, skills sufficient to duplicate the mentor's results were transferred. These data suggest there should be no learning curve for distal hypospadias after training. This report raises several considerations for surgical educators. First, mentors should review their own results, to be certain that they are correctly performing and teaching procedures. Second, programs need to determine key steps for procedures they teach, and then emphasize their optimal performance. Finally, mentors should expect former fellows to report back their initial results of hypospadias repair to be certain lessons taught were learned. Otherwise, preventable complications resulting from technical errors will be multiplied in the children operated by their trainees as they enter independent practice.